2021
DOI: 10.1039/d1cp01491a
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous gold electrodes modified with self-assembled monolayers for electrochemical control of the surface charge

Abstract: Nanoporous gold is modified with self-assembled monolayers (SAMs) of different length. The point of zero charge and the protonation/deprotonation reaction are investigated revealing precise charge control for long-chain SAMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In this context, it may be interesting to investigate if a higher surface coverage would lead to a further decrease in the signal due to NaCl addition. Previous studies of our group 18 using different SAM molecules showed, that a longer linking chain length leads to a better surface coverage. As MPBA is a rather small molecule, a study using boronic acid terminated SAMs with different chain lengths would be of interest to further improve the sensitivity and selectivity to F − .…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In this context, it may be interesting to investigate if a higher surface coverage would lead to a further decrease in the signal due to NaCl addition. Previous studies of our group 18 using different SAM molecules showed, that a longer linking chain length leads to a better surface coverage. As MPBA is a rather small molecule, a study using boronic acid terminated SAMs with different chain lengths would be of interest to further improve the sensitivity and selectivity to F − .…”
Section: Discussionmentioning
confidence: 73%
“…Over the past two decades, nanoporous gold (npAu) prepared by the method of electrochemical dealloying has become a very popular material in many sensing applications due to its good conductivity, high surface-to-volume ratio, free-standing structure and easy tunability. 18–20 However, as gold itself is not very sensitive to F − and furthermore reacts stronger with other halogens such as chlorine ions, 21–23 a modification of its surface, e.g. , by the formation of self-assembled monolayers (SAMs) is needed to make it suitable for fluoride detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, 4-MPBA shows high biological affinity and selectively interacts with sugars, glycopeptides, and glycoproteins. [30][31][32][33] Thus, the ANE/AuNPs surface was modified with 4-MPBA via self-assembly for the recognition and binding of MSLN molecules.…”
Section: Sensing Msln Using the Prepared Microsensormentioning
confidence: 99%
“…A gold electrode coated with 2-mercaptoethanol, which was a short-chain thiol that both increases the electron transport rate, promoting the redox reaction of electron transport, and contains a large number of exposed hydroxyl groups, was used in the experiments. 36,37 Ferrocenemethanol was used as an electrochemical tag to detect the electrochemical behavior with and without catechin and theanine present. Ferrocenemethanol will undergo an oxidation reaction near the tip and then diffuse to the gold electrode.…”
Section: Adsorption Behavior Of Catechin and Theanine In The Presence...mentioning
confidence: 99%